2019
DOI: 10.1159/000502770
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Staff’s Knowledge and Attitudes toward Dementia: A Pilot Study from an Indian Perspective

Abstract: Background: Despite the increased prevalence of dementia in India, reports indicate little awareness of the disease. Symptoms are often misinterpreted or neglected, which could lead to late diagnosis, reducing the choices available regarding future care. Considering that most nurses caring for the elderly will work with people with dementia in the future, there is concern surrounding their ability to meet the needs of these patients, requiring them to obtain the necessary knowledge and positive attitudes for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 32 publications
9
27
0
1
Order By: Relevance
“…However, several participants in our study thought that a person with dementia could improve over time and even become “normal again.” This finding is consistent with the results of previous studies of Indian nursing students [ 17 ], Indian doctors and nurses [ 20 ], and Pakistani adults [ 26 ] in which the participants believed that symptoms may improve over time or even that the person could be cured. This is also in line with the study of Strøm et al [ 25 ], who reported that, although the majority of the healthcare staff in 6 Indian nursing homes answered that Alzheimer disease could not be cured, about half of them said that people with dementia, in rare cases, could recover from the disease. Believing that dementia can be cured could have an impact on how the care is organized.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, several participants in our study thought that a person with dementia could improve over time and even become “normal again.” This finding is consistent with the results of previous studies of Indian nursing students [ 17 ], Indian doctors and nurses [ 20 ], and Pakistani adults [ 26 ] in which the participants believed that symptoms may improve over time or even that the person could be cured. This is also in line with the study of Strøm et al [ 25 ], who reported that, although the majority of the healthcare staff in 6 Indian nursing homes answered that Alzheimer disease could not be cured, about half of them said that people with dementia, in rare cases, could recover from the disease. Believing that dementia can be cured could have an impact on how the care is organized.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in accordance with Poreddi et al [17], who reported that Indian nursing students have an overall positive attitude toward people with dementia. An overall positive attitude toward dementia was also found in the study of Strøm et al [25], in which Indian healthcare staff said that it was rewarding to work with people with dementia; however, they also indicated that they were not familiar with dementia, felt frustrated, and did not know how to help the people.…”
Section: Attitudes Toward People Living With Dementiamentioning
confidence: 60%
See 1 more Smart Citation
“…This nding shows the severity of lack of knowledge in the caretakers that could not reach the next level after four sessions of education and suggest that continuing the education could result in a more noticeable increase in the caretakers' knowledge scores. Previous studies have also shown poor knowledge of the caretakers of nursing homes [17,20,21]. In the qualitative study by Yektatalab and colleagues (2012), the nurses working at a nursing home of Shiraz had limited knowledge about the aspects of care for residents of the nursing home with Alzheimer's disease and provided unprofessional care to these patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…AD Alzheimer's diseaseSouth Korea, and healthcare professionals in Australia, Brazil, China, India, Malaysia, and Spain[8,10,[18][19][20][21][22][23][24][25][26][27]. It was also administered to laypeople in Brazil, and was included as a knowledge resource on the website of the Alzheimer's Association in the USA…”
mentioning
confidence: 99%